Fontes e parcelamento do nitrogênio na cultura do milho - Demari, Gustavo Henrique (2014)
Nitrogen (N) in maize is a major nutrient that influences grain yield, because it participates on numerous metabolic pathways. It is present in the soil organic matter (OM) and it is necessary that it passes through a mineralization process to be available to plants. It is absorbed in the nitrate form (NO3-N) and ammonia (NH4+-N). The most commonly used nitrogen sources are urea [CO (NH2)2] and ammonium sulphate [(NH4) 2SO4]. Due to changes of the soil, N is regarded as a dynamic element with complex reactions, which generate controversy and discussions regarding its source and form of application on corn. Currently the recommendation of nitrogen fertilization to Rio Grande do Sul in maize is 20-30 kg N on the basis of seeding, and the remainders on coverage between phenological stages V4 to V6. The literature states results which conflict seasons of nitrogen management on corn, so the hypothesis that the parcelling and the source can bring loss or benefits related to the number of applications and greater efficiency, there may be differences between sources and hybrid. Therefore, the aim of this study was to evaluate the effects of splitting nitrogen in some plant parameters and on the final yield of two maize hybrids using urea and ammonium sulphate. This study was conducted in the municipality of Tenente Portela in Rio Grande do Sul. The randomized block design was used, arranged in a factorial scheme (2 x 2 x 11 x 2) on three replications, with two agricultural seasons, two hybrids, eleven periods of application and two sources. Evaluations were plant height, ear insertion height, prolificacy, ear diameter, number of rows per ear, number of kernels per row, ear mass, cob diameter, mass of grains, weight of thousand seeds and grain yields. Nitrogen application at different stages influencing plant height and ear height, number of rows per ear and yield. There was no response in grain yield of maize with the use of different sources of nitrogen, however, was superior when applied in the early growth stages.